Analysis of children’s self-confidence in transition activities from pre-school to kindergarten - Apriyani, Erni Tresna; Muqodas, Idat; Nikawanti, Gia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
Self-confidence is one of the indicators of school readiness. To build school readiness, teachers can carry out transition movement activities through building foundation skills. The purpose of this study was to investigate the self-confidence of early childhood students and the process of PAUD to SD transition activities conducted by teachers during learning activities. This research uses a qualitative approach with a case study research design; data were collected through observation, interviews, and documentation. This research involves 15 students and one teacher who were selected through purposive sampling. Data analysis uses the Miles and Huberman analysis model. The results of the study show that children’s self-confidence is evident in the transition activities from preschool to elementary school through the habituation of six foundational skills. The habituation of these six foundational skills can be used to build a child's self-confidence. This research could be improved if conducted in a more in-depth and detailed manner over a longer period.